Nilai Pendidikan Karakter Dalam Makna Dan Simbol Tari Nyengcelak Puspa Ningati Pada Penari Remaja Di Sanggar Gandes Pamantes - Putri Setiadi, Wafa Zahra; Kartika Mutiarasari; Selly Oktarani (Jurnal Pendidikan Tari, 2024)
The purpose of this study is to analyze the value of character education in the meaning and symbols of the Nyengcelak Puspa Ningati dance in adolescent dancers at the Gandes Pamantes Studio. This study uses a descriptive qualitative method. The concept of meaning and symbols refers to Roland Barthes' Semiotics which states that Barthes distinguishes between denotation, which is the literal or descriptive meaning of a sign, and connotation, which is an additional meaning that is conceptual or cultural. By analyzing both cans. Keywords: Character Education, Nyengcelak Puspa Ningati, Meaning and Symbols of Dance